An effective procedure for skin stiffness measurement to improve Paediatric Burn Care. Issue 5 (August 2019) - Elrod, Julia; Müller, Bettina; Mohr, Christoph; Meuli, Martin; Mazza, Edoardo; Schiestl, Clemens
Highlights: Nimble measurement of scar stiffness in paediatric patients is reliable. Intra- and interobserver variability is superior to the Cutometer. High usability is ensured due to light weight, small dimension and disposability. Abstract: Background: The objective evaluation of scar quality plays a crucial role in improving burn surgery and scar rehabilitation. Suction-based skin measurements were proposed as a method to objectively determine the mechanical properties of scars, yet their use is limited, in particular for paediatric burn care. A new device was developed which provides essential advantages for scar assessment. The aim of this study was to assess its reliability, intra- and interobserver variability. Methods: The new device, "Nimble", consists of a lightweight probe that measures the negative pressure needed to obtain a predefined tissue elevation, revealing information on the stiffness of the tissue. 29 former paediatric burn patients were included. Three observers measured the tissue stiffness of a predefined location on the scar and on healthy skin using the Nimble, and the established suction device, the Cutometer ® . The reliability of both instruments in distinguishing between healthy skin and scar was assessed by means of the intraclass correlation coefficient. Results: The Nimble successfully differentiated between scar tissue and healthy skin in 92%, the Cutometer in 80% of the patients (p < 0.05). Inter- and intraobserver variability of the Nimble (ICCs) were excellent. For the majority of the calculated ICC values the Nimble exceeded the Cutometer ® . Conclusion: The new device enables reliable and safe measurement of the stiffness of scars. Measurements are less susceptible to patient non-compliance and observer dependency. The Nimble might therefore constitute an easy to use tool for the systematic assessment of scars, thus supporting decision-making in paediatric burn care.